Status of Ganges River dolphin Platanista gangetica (Lebeck, 1801) in the lower stretch of the Ganga River, India, with emphasis on threats, conservation, and recommendations - Das, Basanta Kumar; Bhakta, Dibakar; Johnson, Canciyal; Chanu, Thangjam Nirupada; Ramteke, Mitesh; Chauhan, Suraj Kumar; Ray, Archisman; Nandy, Saurav; Kunui, Arghya; Roy, Shreya; Mohanty, Trupti Rani; Tiwari, Nitish Kumar; et al. (Frontiers in Ecology and Evolution, 2025)
The Ganges River dolphin (GRD), Platanista gangetica, is one of the most endangered cetaceans in the world and is seriously in danger from dams and barrages, restricted river flows, bycatch, pollution, etc. The GRD is a freshwater dolphin, commonly known as "susu", one of the four freshwater cetacean species in the world. The GRD primarily inhabits freshwater and estuarine zones, never venturing into the sea. The present study (2022–23) conducted a seasonal survey at the Bhagirathi–Hooghly River systems of West Bengal to investigate the abundance, habitat use, and potential threats in the lower stretches of the River Ganga. During the survey we recorded 303 dolphins with higher numbers of individuals in dry season (0.47 dolphins/linear km) than in the wet season (0.29 dolphins/linear km). The study also confirmed that freshwater dolphins primarily inhabit river confluences, or tributary junctions, and river meanderings with abundant prey-fish. The rapidly declining Ganga River dolphin faces numerous potential threats, including aquatic pollution, habitat destruction, net entanglements, overfishing with destructive fishing gear, agricultural and industrial effluents, vessel collisions, sand mining, and a lack of awareness about dolphin conservation. No, or regulated, fishing in dolphin hotspot locations, and ensuring as well as maintaining enough dry season flows, are likely to help preserve dolphin numbers and reduce competition for fish with fishermen.